Cardiac chamber volumes and left ventricular mass in people living with HIV and matched uninfected controls. Issue 10 (9th September 2020) - Krebs‐Demmer, L; Ronit, A; Sigvardsen, PE; Lebech, A‐M; Gerstoft, J; Knudsen, AD; Fuchs, A; Kühl, JT; Nordestgaard, BG; Kofoed, KF; Nielsen, SD
Abstract : Objectives: People living with HIV (PLWH) have increased risk of cardiovascular diseases compared with uninfected populations. We assessed structural cardiac abnormalities and their associated risk factors in well‐treated PLWH and uninfected controls using multidetector computed tomography (MDCT). Methods: People living with HIV and age‐ and sex‐matched uninfected controls underwent MDCT to determine left atrial volume (LAV), left ventricular diastolic volume (LVDV), right ventricular diastolic volume (RVDV) and left ventricular mass (LVM). All outcomes were indexed to body surface area (BSA) (LAVi, LVDVi, RVDVi and LVMi). Results: A total of 592 PLWH and 1184 uninfected controls were included in the study. PLWH had smaller mean (SD) LAVi [40 (8) vs . 41 (9) mL/m 2 ; P  = 0.002] and LVDVi [61 (13) vs . 65 (14) mL/m 2 ; P  < 0.001] but larger RVDVi [89 (18) vs . 86 (17) mL/m 2 ; P  < 0.001] than uninfected controls. HIV was independently associated with 7 mL (95% CI: −10 to −3) smaller LVDV, and with 12 mL (95% CI: 8–16) larger RVDV, and 4 g (95% CI: 1–6) larger LVM after adjustment for cardiovascular risk factors and BSA. Large RVDV in PLWH was not associated with obstructive lung function. Conclusions: HIV was independently associated with smaller LVDV and larger RVDV and LVM. Alterations in cardiac chamber volumes in PLWH were mainly minor. The clinical impact of these findings is uncertain, but it seems unlikely that alterations in cardiac chamber volumes explain the increased burden of cardiovascular disease previously observed in PLWH.